ANALISIS SEBARAN POTENSI SEKTOR UNGGULAN MENGGUNAKAN METODE LQ (LOCATION QUESTION) DAN DLQ (DYNAMIC LOCATION QUOTIENT) DI KABUPATEN KONAWE UTARA - Woraya, Selfira; febriansyah, Alid; Hemon, M Tufaila (Universitas Nusa Cendana, 2025)
The potential of a region can be explained through the base sector, which is a sector that is able to fulfill local needs and be exported outside the region. Geographic Information System (GIS) is used to present spatial data of regional potential in the form of maps. This research was conducted in North Konawe Regency to identify leading sectors and their spatial distribution. Data were obtained through interviews and observations, then analyzed using the Location Quotient (LQ) and Dynamic Location Quotient (DLQ) methods. The analysis showed that the current leading sectors are agriculture, forestry and fisheries (LQ = 1.75) in Lasolo Sub-district; mining and prospecting (LQ = 1.02) in Langgikima Sub-district; and health services and social activities (LQ = 1.19) in Asera Sub-district. Potentially leading sectors in the future are mining and sedimentary (DLQ = 1.04) and processing industry (DLQ = 4.02). These findings can serve as the basis for development planning based on regional potential.